Islamic Education as an Ethical Mechanism in Responding to Social Diversity: A Contextual Analysis of Indonesia and Malaysia - Achmad Saifur Rijal; Muhammad Akhsanul Husna; Tedi Kholiluddin; Muhammad Ali Subkan (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
Social diversity has become an inherent characteristic of contemporary societies, particularly in Muslim-majority countries such as Indonesia and Malaysia. While Islamic education is often associated with moral instruction and religious moderation, its ethical function in shaping social responses to diversity remains insufficiently explored. This study aims to examine Islamic education as an ethical mechanism in responding to social diversity within the contexts of Indonesia and Malaysia. Using a qualitative–conceptual approach through library research, the study analyzes scholarly literature, academic works, and relevant policy documents on Islamic education, ethics, and pluralism. The findings show that Islamic education operates as an ethical mechanism through humanistic orientation, dialogical engagement, moral responsibility, and contextual sensitivity, enabling ethical engagement with diversity beyond rigid normative prescriptions. The analysis also reveals contextual variations in how these ethical mechanisms are articulated in Indonesia and Malaysia, shaped by differing socio-cultural and institutional settings. Due to its literature-based design, this study is limited to conceptual interpretation and does not claim empirical generalization. Nevertheless, the study contributes originality by reframing Islamic education as an ethical mechanism, offering conceptual value for understanding the role of education in plural societies and informing future empirical research.